2014
DOI: 10.1371/journal.pone.0084291
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding Reveals Limited Accuracy of Identifications Based on Folk Taxonomy

Abstract: BackgroundThe trade of plant roots as traditional medicine is an important source of income for many people around the world. Destructive harvesting practices threaten the existence of some plant species. Harvesters of medicinal roots identify the collected species according to their own folk taxonomies, but once the dried or powdered roots enter the chain of commercialization, accurate identification becomes more challenging.MethodologyA survey of morphological diversity among four root products traded in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 55 publications
(89 reference statements)
1
48
0
Order By: Relevance
“…Alternatively, the traditional products may consist of different species than those mentioned in the pharmacopoeia. Similar research in Morocco also showed a high level of substitution and suggested that, in addition to the options above, gradual substitution over time of one species for another could explain the discrepancy [9,22]. Some examples of cases where DNA barcoding showed samples to be completely different from the putative species in this study are “Marzeh” and “Maryam goli.” The vernacular name “Marzeh” refers to either Satureja laxiflora C.Koch or S .…”
Section: Discussionsupporting
confidence: 78%
“…Alternatively, the traditional products may consist of different species than those mentioned in the pharmacopoeia. Similar research in Morocco also showed a high level of substitution and suggested that, in addition to the options above, gradual substitution over time of one species for another could explain the discrepancy [9,22]. Some examples of cases where DNA barcoding showed samples to be completely different from the putative species in this study are “Marzeh” and “Maryam goli.” The vernacular name “Marzeh” refers to either Satureja laxiflora C.Koch or S .…”
Section: Discussionsupporting
confidence: 78%
“…Species delimitation based on molecular data is being developed but requires many accessions as well as many loci [58]. The most reliable approach to DNA barcoding of plants is the creation of high-quality specific sequence reference databases for the identification of targeted species [31,37,59]. Such databases should include reference to a specific taxonomic voucher that has been determined by a professional taxonomist.…”
Section: Species Delimitation and Inter-and Intraspecific Variationmentioning
confidence: 99%
“…Microscopic identification can be applied to whole, fragmented, or powdered material, and it can be helpful in cases where plant species are undistinguishable merely based on their macroscopic characteristics [30]. These methods are very time-and cost-efficient; therefore, they are very widely applied for authentication purposes of traditional herbs [129,130]. Also, herbal pharmacopeia monographs usually contain a detailed description of macroscopic and microscopic drug characteristics, allowing a first assessment of identity and, in some cases, the identification of common adulterants [30,131].…”
Section: Botanical Macroscopic and Microscopic Authentication Methodsmentioning
confidence: 99%